el-İkmâl fî ref’i’l-irtiyâb ani’l-mü’telif ve’l-muhtelif mine’l-esmâ’ ve’l-künâ ve’l-ensâb - 880-01 İbn Mâkûlâ, 1030-1082. (Beyrut)
7 cilt (1. c. 592, 2, 2, 8, [1] sayfa ; 2. c. 587, 10 sayfa ; 3. c. 404, [2] sayfa ; 4. c. 576, [1] sayfa ; 5. c. 285, [1] sayfa ; 6. c. 424, [1] sayfa ; 7. c. 472 sayfa)